Evaluation of Buffalo Health and Prevalence of Metabolic Disorders in Pulivendula: A Urine Analysis Approach - Raj, T. Amala Arockia; Jayasankar, A.; Naik, M. Muniya; Reddy, H. Ramasubba; Mohan, K. Chandra; Beebi, B. Jameela; UdayKiran, V. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Aim: The study aims to evaluate the health status of buffaloes in selected villages of Pulivendula, detect potential metabolic disorders, and assess the prevalence of common health issues using urine analysis via the dipstick method. Objectives: The main aim of this study is to identify abnormalities, correlates the findings with nutrition and health data and emphasizes student participation in community-based animal health programs. Materials and Methods: A total of 25 buffaloes from five villages in the Pulivendula region were randomly checked as part of the study. The dipstick method was chosen for urine sample collection and analysis because of its ease of use, affordabilitys and speedy findings. Tests were conducted on parameters including Blood, Bilirubin, Nitrite, Leucocytes, Sp. Gravity Glucose, Protein, pH, Urea, RBC and Ketones. Students also completed surveys that yielded information about the diet, living circumstances, and overall health of the buffaloes. Results and Discussion: The investigation found that a less number of buffaloes had aberrant urine parameters, indicating subclinical illnesses. Proteinuria and ketonuria were more common in buffaloes from settlements with limited access to quality feed and water. The study results revealed a link between dietary behaviours and observed urine abnormalities, highlighting the need for better nutritional management and health monitoring in these locations. This study highlights the importance of the dipstick method in routine veterinary health checks, as well as the need for focused interventions to improve buffalo health and productivity in the Pulivendula region.